A Knowledge-Based Model of Strategic Alliances in Education: An SLR for Multi-Dimensional Sustainable Value Creation (SDGs 4, 8, 9, 13) - Yusuf, Yusuf; Bustamam, Ummi Salwa Ahmad (Assyfa Journal of Multidisciplinary Education, 2025)
Strategic alliances play a crucial role in business sustainability; however, the lack of an educational model that facilitates these alliances is a significant barrier to shared value creation at both operational and educational levels. The purpose of this SLR is to synthesize the role of strategic alliances in entrepreneurship education, focusing on the formulation of a Shared Value Creation (CSV) model that impacts the four pillars of the Sustainable Development Goals (SDGs). Using a conceptual and integrative systematic literature review (SLR) approach, this study analyzes Scopus- and Web of Science (WoS)-indexed literature that links strategic alliances, entrepreneurship education, and shared value creation. Key findings demonstrate the critical need to integrate Knowledge Management Capabilities and Inter-organizational Trust as prerequisites for successful alliances in education. This SLR constructs a structured Conceptual Model of Strategic Alliances in Education, which facilitates the creation of balanced shared value (Profit, People, Planet) in the curriculum. Conclusion: The proposed model makes a significant contribution, offering a transformative roadmap for implementing a curriculum in educational institutions and industry partners. This model enables industry alliances to integrate sustainability across the pillars of Education (SDG 4), Economy (SDG 8), Innovation (SDG 9), and Environment (SDG 13).